The Cow That Stole Christmas: Framing the First U.S. Mad Cow Crisis - Marcus A. Ashlock; D. Dwayne Cartmell II; Danna B. Kelemen (Journal of Applied Communications, 2006)
The discovery of bovine spongiform encephalopathy (BSE) in the United States made an impact on the beef industry. Determining how the BSE outbreak was framed by the news media is significant because research indicates that media shape public perceptions. This study examined how several key newspapers framed the 2003 outbreak of BSE in the United States. Determining how the media framed this issue can help communicators ensure bias-free media coverage of similar issues in the future. The study followed established framing analysis categories identified from the literature. There were 149 articles identified in The Washington Post, The Seattle Times, and USA Today for investigation in this study. Findings showed that the BSE issue was framed as an industry crisis and that the tone of the articles and headlines portrayed the beef industry negatively. When compared to the other two newspapers, USA Today framed the issue differently, with economic calamity being the dominant frame. The most heavily cited sources in the articles were government officials. This study recommends that media professionals avoid framing an issue for the public, focusing instead on reporting news in an objective and unbiased manner. Further research is recommended to examine the impact of tone and frame on specific audiences.